Swipe this! : the guide to great touchscreen game design - Rogers, Scott (Wiley, 2012)
"Eager to start designing games for tablets but not sure where to start? Look no further! Gaming guru Scott Rogers has his finger on the pulse of tablet game design and is willing to impart his wisdom and secrets for designing exciting and successful games. As the creator of such venerable games as God of War, the SpongeBob Squarepants series, and Pac-Man World, to name a few, Rogers writes from personal experience and in this unique book, he hands you the tools to create your own tablet games for the iPad, Android tablets, Nintendo DS, and other touchscreen systems. [The book] covers the entire tablet game creation process, placing a special focus on the intricacies and pitfalls of touch-screen game design; explores the details and features of tablet game systems and shows you how to develop marketable ideas as well as market your own games; offers an honest take on what perils and pitfalls await you during a game's pre-production, production, and post-production stages; features interviews with established tablet game developers that serve to inspire you as you start to make your own tablet game design. Swipe This! presents you with an in-depth analysis of popular tablet games and delivers a road map for getting started with tablet game design."--Publisher's description.